NEURAL NETWORKS AS A CATALYST FOR TRANSFORMATION OF PREPRESSURE LITERATURE (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the role of neural network technologies in the teaching of literature. Given the scarcity of specialized research on this topic in available literature, the focus is placed on a single yet illustrative case—the use of a neural network to write a school essay—as well as on the broader discussion regarding the acceptability and risks of using artificial intelligence in education. Insights are also drawn from related disciplines—such as the visual arts, foreign languages, and journalism—where the use of generative neural networks has already been documented in greater detail. It was concluded that the question of the role of neural networks in literary education is currently more pressing than it is well-studied, and that it requires dedicated methodological research.